Determination of operative parameters for production of saponins extract of Cucumis dipsaceus “hedgehog gourd” - Seijas Velásquez , Segundo (2021)
Cucumis dipsaceus " hedgehog gourd ", is a plant species of the family of cucurbits considered as weeds in our region, whose fruit has secondary metabolites of industrial and pharmacological importance highlighting among them the flavonoids, glycosides, alkaloids, tannins and saponins. The latter compound has properties such as surfactant, foaming agent, anti-inflammatoryagent and hepatoprotection. Due to the properties of saponins, the present study was proposed whose main objective was to determine the operating parameters: temperature, time and solid/solvent ratio in the production process of saponin extract from the fruit of Cucumis dipsaceus " hedgehog gourd “. The study began with a pre-treatment of the fruits which consisted of cleaning, pulping and drying operations. The experiments were carried out through extractive laboratory-level tests to determine the optimal operating parameters. Then the design of the equipment involved in the process was carried out: vacuum distillation, filtering and drying, as well as a computer program in Visual Basic 10 was obtained in order to proceed to the respective pilot scaling. To determine the presence and concentration of saponins in the final product, assays of red blood cell hemolysis and foam or afrosymmetric test were performed. A yield of 73,5% was obtained in the production of saponins using the operating parameters: solid / solvent ratio 1, temperature 600C and extraction time 30 minutes.